Quality control for bored pile construction - Bandong, Ederlyn J.
This paper provides detailed construction methodologies for bored piles. The main purpose is to determine which of these processes affect the performance of the piles. Possible pile defects and the corresponding mitigation procedures are determined. The method statements given by three construction companies, namely Advanced Foundations Construction System Corporation, Bauer Foundation Philippines, Inc., and Trevi Foundations Philippines, are compared and are assessed based on their adherence to the international standard, BS EN 1536, they have adopted. Site visits and the provided checklist verify the actual construction process. Samples of Crosshole Sonic Logging test results in certain projects were also analyzed to prove that strict compliance to the quality assurance and quality control system result to good quality piles.